The Challenges of Converting Municipal Solid Waste (MSW) to Energy in Lahore - Chaudhry, Waseem Ajmal (Journal of Pakistan Administration, 2025)
It was a sweltering afternoon in June 2013. Mr. Chaudhry, Managing Director (MD) Lahore Waste Management Company (LWMC), was sitting in his office and anxiously contemplating upon his options on how to pick up the gauntlet thrown at him by the Chief Minister (CM), Punjab. He used to seek great inspiration from Prometheus, his dialogical self, in such challenging situations.  Why do you seem worried?” Prometheus asked the MD. The CM desires that I should plan and execute a power plant by converting municipal solid waste into electrical energy.The MD said, “He wants to get it done tomorrow. He has made ambitious promises with the electorate to end energy crises in the country in the shortest possible time, therefore, he is exploring every avenue to achieve his political goals and there is zero tolerance for any non-performance.
Keywords: Challenges; Municipal Solid Waste (MSW); Energy; Lahore; gauntlet